Limited factor VIIa surface localization requirement of the factor VIIa–induced overall thrombin generation in platelet‐rich hemophilia A plasma - Egon Persson; Mette Winther (Research and Practice in Thrombosis and Haemostasis, 2019)
Abstract Background Thrombin generation assay (TGA) and thrombelastography (TEG) are increasingly employed, global, in vitro methods for assessment of the procoagulant potential of plasma/blood and possibly ideally suited tools to monitor, for example, therapy with recombinant factor VIIa (FVIIa). It remains controversial to what extent results obtained with spiked and postinfusion samples reflect the outcome in patients. Objective To characterize the TGA response to FVIIa in hemophilic plasma and compare with TEG data. Methods Hemophilia A (HA) was induced in platelet‐rich plasma (PRP) from healthy volunteers, followed by spiking with FVIIa, γ‐carboxyglutamic acid (Gla)‐domainless FVIIa or V158D/E296V/M298Q‐FVIIa (FVIIaDVQ). Samples were triggered with tissue factor and analyzed by TGA and TEG in parallel. Results Addition of 25 nmol L−1 FVIIa to HA PRP normalized TEG parameters angle and R time, as well as TGA lag time, but had poor effects on the thrombin peak height and velocity index. All parameters (at least) returned to normal levels either upon adding a much higher concentration of FVIIa (~1500 nmol L−1) or by using the superactive variant FVIIaDVQ. Surprisingly, Gla‐domainless derivatives of FVIIa and FVIIaDVQ also yielded considerable effects in HA PRP. Conclusions The good general responses to clinically effective concentrations of FVIIa (25 and 75 nmol L−1) seen in TEG analyses, as well as for TGA lag time, were accompanied by far‐from‐normal thrombin peaks. A near‐normal thrombin peak response required the presence of considerably higher FVIIa activity but, intriguingly, relied only marginally on a functional Gla domain (ie, on platelet surface localization).